(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This research aimed to study the multi-level ammoniation on the digestibility of palm press fiber (PPF) through in vitro methods. Materials and Methods: This research was determined using a complete randomized design of three ammoniation treatments on PPF with three replications: (1) untreated PPF (Con), (2) ammonia treatment 4% (A-4), and (3) ammonia multi-levels of 6%, 4%, and 2% (A-Mul). Results: The results showed a significant effect on the chemical composition of feed in the A-Mul treatment compared to Con (p < 0.05) and a non-significant effect when compared to the A-4 treatment. Overall, the content of crude protein, ether extract, and crude fiber in the A-Mul treatment increased. Except in the dry matter (DM), neutral detergent fiber and acid detergent fiber decreased. The results of the in vitro analysis showed an increase in digestibility of DM, Organic matter digestibility, N-NH3, and volatile fatty acids (VFA) in ammoniation treatment. N-NH3 and VFA showed non-significant differences between treatments A-4 and A-Mul (p > 0.05). Conclusion: Multi-level ammoniation has affected the loosening of the fiber fraction bonding in the PPF, thereby changing the value of the chemical composition and the digestibility of PPF. Multi-level ammonia can be used as an alternative to processing high-fiber feed. J. Adv. Vet. Anim. Res., 8(2): 230-236, June 2021